Cérebro social, mentalização e psicopatologia evolutiva. Indicações da psicopatologia dos primatas não humanos para a psicopatologia humana - Lencastre, Marina Prieto Afonso (Trabalhos de Antropologia e Etnologia, 2020)
Research on human social brain shows its evolutionary homology with the brain and social motivations and behaviors of other primates. The psychopathology of non-human primates can help refound human psychopathology. Nevertheless, schizophrenia and related psychotic disorders may be specific human psychopathologies, as they imply exclusive cognitive habilities of the human brain, such as second and third order mentalization capacities, symbolization and the production of internal mental realities.